Antiviral Agents – Benzazine Derivatives - Mochulskaya, Nataliya N. (Chem Heterocycl Compd (N Y), 2021)
[Image: see text] The review outlines the results of studies of the antiviral activity of quinoline, quinoxaline, and quinazoline derivatives published over the past 5 years. The supplied data indicate the enormous potential of benzazines for the design of effective antiviral drugs.